"What if We Explore…" Promoting Engaged Learning and Collaboration with MOUNTAIN RESCUE. (October 2022) - Bressler, Denise M.; Tutwiler, M. Shane; Siebert-Evenstone, Amanda; Annetta, Leonard A.; Chen, Jason A.
Background: According to the Committee on STEM Education, K-12 science students need access to learning experiences that promotecollaboration andengagement . To fill that void, we need to develop activities that stimulate engaged learning and scaffold effectivecollaboration . K-12 teacher candidates see value in utilizing games for this purpose. Specifically, tabletop science games can help teachers engage students inscience learning and scaffoldcollaboration . Aim: For this study, we designed a collaborative, STEM -themed card game called MOUNTAIN RESCUE and explored its capacity to promote engaged learning andcollaboration . Method: Four groups ofSTEM campers (n = 14) in a suburban Mid-Atlantic region played MOUNTAIN RESCUE. All groups had a mix of boys and girls. Play-testers ranged from 10–13 years old. Thetabletop game took approximately 30-minutes. During gameplay, players embodied uniqueSTEM roles: physicist, chemist, structural engineer, and electrical engineer. They collaborated to solve challenges related to electricity, physics, chemistry, and engineering design. Discourse was audio-recorded throughout gameplay. Immediately after gameplay, self-report survey data were collected to assessflow and perceptions of collaborative learning. Results: Findings demonstrated that the game promotedengagement andcollaboration . Specifically, students had aflow -like experience and felt positively about the game's value for collaborative learning. Utterances demonstrating activeengagement and constructive thinking became more group-focused over time. Conclusion: This study contributes to science education by demonstrating potential benefits of a well-designed, low-tech, science learning environment or—in other words—atabletop game .